Liochlaena sichuanica—a new species from the Tibetan Spur and diversification in Liochlaena (Jungermanniaceae, Marchantiophyta) - Bakalin, Vadim; Vilnet, Anna; Ma, Wen Zhang (Phytotaxa, 2018)
Liochlaena sichuanica is described using an integrative taxonomy approach including morphological, geographical and molecular phylogenetic studies. The species is characterized by dioicous sexuality, distinctly papillose leaf surface and large cells in the midleaf. This is the third known taxon in the genus and, with the limited data in hand, also has a narrow geographic distribution. It may represent a diploid derivative of L. subulata, as does L. lanceolata, but with a narrower area of distribution that seems to be restricted to the northern part of the southeastern spur of the Tibetan Plateau. The distribution of Liochlaena sichuanica could be treated both as the result of recent speciation and as the result of a drastic decrease in area.